MAKNA ASOSIATIF DALAM KITAB AYUB - Daake, Kartini Natalia T.; Pamantung, Rina P.; Sigarlaki, Stephani J. (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2022)
ABSTRACT                                              Kartini N.T Daake¹                                        Dr. Rina Pamantung, M.Hum²                                     Stephani J. Sigarlaki, S.S M.Hum³     This research entitled "The Associative Meaning in Book of Job". The problems of this research focus on the five types of Associative Meaning, that is connotative meaning,social meaning, affective meaning, reflected meaning and collective meaning and their descriptions in the Book of Job. The aims of the research are to identify, classify the verse into the five types of associative meanings, and to analyze the verses in the Book of Job using Semantics approach. This research uses descriptive method, supported by Leech's theory. In collecting data, the writer focused on reading the words, phrases, or sentences in every verse from chapter 1-42.The writer found 19 words, 8 pharases, and 17 sentences which contains the five types of associative meanings. The result of this research that the writer found that are 14 date of connotative meaning, 5 date of social meaning, 10 date of affective meaning, 5 date of reflective meaning, and 10 date of collocative meaning in the Book of Job.Keywords:Meaning, Associative Meaning, Book of Job, Descriptive Analysis.